Peran lembaga keuangan mikro syariah dalam meningkatkan kesejahteraan masyarakat: Studi kasus di Indonesia - Khuluddiyah, Zulaikhatul (Maliki Interdisciplinary Journal, 2024)
Sharia Microfinance Institutions (SMFI) are financial institutions that aim to help and provide financing to the lower class of society and reduce poverty. The purpose of this research is to find out the important role of SMFI in improving the welfare of the Indonesian people. Desk research or literature study is the method used by the researcher in this article to obtain the necessary information. This method involves the use of various literature sources. Since the data obtained is in the form of words or descriptions, a qualitative approach is used. This desk research is based on the search for previous research that is relevant or related to the topic discussed. The results of this study show that Sharia Microfinance Institutions (SMFI), such as Baitul Mal Wa at-Tamwil (BMT), have an important role in improving the welfare of the community, especially among the lower middle class. By providing access to finance in accordance with sharia principles, SMFI play a vital role in reducing economic disparities and empowering micro and small businesses. SMFI also provide an alternative for those who find it difficult to access funding from conventional financial institutions such as banks. In addition, SMFI act as a driver of the real sector by providing financing to businesses in the sector, as well as a social institution that manages zakat, infaq and sadaqah funds to be distributed to those in need.